Characterization of PAN-1, a Carbapenem-Hydrolyzing Class B β-Lactamase From the Environmental Gram-Negative Pseudobacteriovorax antillogorgiicola - Kieffer, Nicolas; Poirel, Laurent; Fournier, Claudine; Haltli, Brad; Kerr, Russel; Nordmann, Patrice (Frontiers in Microbiology, 2019)
The gene encoding the metallo-β-lactamase (MβL) PAN-1 was identified in the genome of the environmental Gram-negative species Pseudobacteriovorax antillogorgiicola. PAN-1 shares 57% amino-acid identity with the acquired MβL SPM-1, its closest relative. Kinetic parameters performed on purified PAN-1 showed it displayed a hydrolytic activity toward most β-lactams including carbapenems, but spared cefepime and aztreonam. These results further highlight that environmental bacterial species may be reservoirs of MβL encoding genes.